Study of the comparative effects of fluoxetine and ziprasidone in albino rats by using tail suspension test model - Kumar, Hansraj; Chandra, Akash; Keshari, Uma Shankar Prasad; Kumar, Rajiv (International Journal of Research in Medical Sciences, 2020)
Background: Depression is a group of disorders results from a combination of multiple etiologic factors- genetic, biochemical, psychodynamic and socio-environmental. A depression consists of following clinical features as sadness, apathy, changes in sleep pattern, impaired concentration, feeling of shame or guilt and thoughts of dying or death. Fluoxetine and Ziprasidone both are used for the treatment of Depression in human being. Fluoxetine is Selective serotonin reuptake inhibitors (SSRI) and Ziprasidone is atypical antipsychotic. Methods: Healthy male albino rats weighing between 150-200 grams were taken for the present study. Study animals were divided into three groups randomly with each group consisting of ten animals. Drugs were powdered with help of mortar and pestle and mixed in gum acacia solution. Appropriate volume of the freshly prepared solution was administered orally daily between 9 am to 10 am to all animal as per their individual body weight. Group A administered 1ml of 0.9% normal saline orally and serves as control group. Group B administered 0.4 mg of fluoxetine orally. Group C administered 1.6 mg of ziprasidone orally. Animals were evaluated for antidepressant activity using two models – Tail suspension test and Forced swimming test. Results: The results in the tail suspension test were assessed by duration of immobility in 6 minutes duration. Antidepressant activity is indicated by the reduction in the duration of immobility i.e. lesser the duration indicates more effectiveness of the drug. Conclusions: There is significant difference in antidepressant activity of fluoxetine with antidepressant activity of ziprasidone.